Pengaruh Daya Tarik Iklan dan Brand Trust Terhadap Minat Beli Konsumen Produk Kosmetik Pada Pengguna E-Commerce Sociolla (Studi Kasus Kelurahan Tanjung Rejo) - Pasaribu, Tiara Hotria; Aramita, Finta (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The rapid pace of economic growth and continuously developing markets encourage intense competition between companies. In addition, current technological developments will, of course, have a significant influence on companies in marketing the products they sell so that consumers can accept them in various ways. This research aims to see how big the influence is advertising attractiveness (X1) and brand trust (X2) on Purchase Interest (Y) among Sociolla E-commerce Users in Tanjung Rejo Village. This study uses a quantitative approach. The population in this study was 6,650 people living in the Tanjung Rejo sub-district. That data was obtained from a questionnaire using a Likert scale distributed via Google Form, which contains the questionnaire. Sample In this research, 100 samples were taken using the Slovin formula and technique The sample collection used was non-probability sampling in the form of purposive sampling. This research data was analyzed using analysis multiple linear regression with SPSS 22.0 tools. This research shows that the advertising attractiveness variable is partially influential, positive, and significant on purchasing interest, and brand trust variables have a positive and significant effect on buying interest. Meanwhile, the advertising attractiveness and brand trust variables simultaneously have a positive and significant effect on consumer buying interest in cosmetic products among Sociolla e-commerce users in the Tanjung Rejo sub-district, with an R Square value of 0.563 or 56.3%.